Effects of Acute Sleep Deprivation Resulting from Night Shift Work on Young Doctors - Sanches, Inês (2015)
Introduction: To evaluate sleep deprivation and its effects on young physicians in relation to concentration capacity and psychomotor performance. Material and Methods: Eighteen physicians aged 26 - 33 years were divided into 2 groups: non-sleep deprived group (with no night work) and sleep deprived group (minimum 12 hour of night work/week). We applied Pittsburgh Sleep Quality Index to screen the presence of sleep pathology and Epworth Sleepiness Scale to evaluate subjective daytime sleepiness; we used actigraphy and sleep diary to assess sleep hygiene and standard sleep-wake cycles. To demonstrate the effects of sleep deprivation, we applied Toulouse- Piéron’s test (concentration test) and a battery of three reaction time tasks after the night duty. Results: Sleep deprived group had higher daytime sleepiness on Epworth Sleepiness Scale (p < 0.05) and during week sleep deprivation was higher (p < 0.010). The mean duration of sleep during the period of night duty was 184.2 minutes to sleep deprived group and 397.7 minutes to non-sleep deprived group (p < 0.001). In the Toulouse-Piéron´s test, the sleep deprived group had more omissions (p < 0.05) with a poorer result in concentration (p < 0.05). Psychomotor tests that evaluated response to simple stimuli revealed longer response latency (p < 0.05) and more errors (p < 0.05) in Sleep deprived group; in reaction to instruction test the sleep deprived group showed worse perfection index (p < 0.05); in the fine movements test there was no statistically significant difference between the groups. Discussion: Acute sleep deprivation resulting from nocturnal work in medical professions is associated with a reduction in attention and concentration and delayed response to stimuli. This may compromise patient care as well as the physician’s health and quality of life. Conclusion: It is essential to study the effects of acute sleep deprivation on the cognitive abilities and performance of health professionals.